Sickness absenteeism among nurses after the COVID-19 pandemic: A study protocol - Halim Ismail; Zhe Shen Huam; Sheng Qian Yew; Hanis Ahmad; Chan Chee Hoong David; Mohd Hafiz Baharudin; Nor Azila Muhd Aris (PLoS ONE, 2025)
Introduction Sickness absenteeism among the nurses in Malaysia is not fully understood. Complicated with the increase in workload and mental stress during the COVID-19 pandemic and the manifestation of long COVID-19 symptoms, there is a need for an updated insight on the prevalence and the risk factors of sickness absenteeism among nurses in Malaysia. As such, we designed a study protocol that assess the prevalence and risk factors of sickness absenteeism among nurses in Malaysia in the post-COVID-19 pandemic era. Materials and methods This is a correlational cross-sectional study. The sociodemographic and clinical questionnaire, sickness absenteeism questionnaire, job characteristics questionnaire, Demand-Control-Support Questionnaire (DCSQ), Work-Related Strain Inventory (WRSI), Work and Family Conflict Scale (WAFCS), the COVID-19-related workplace worries questionnaire, as well as the Depression, Anxiety, and Stress (DASS-21) questionnaire will be randomly distributed to 166 nurses from October 2024 to May 2025. Discussion While physical illnesses, psychological disorders, job-related factors, and sociodemographic factors have been identified as risk factors to sickness absenteeism among healthcare professionals in general, the role of these risk factors in causing sickness absenteeism among the nurses remains unclear. Additionally, the increased stress and workload faced by nurses during the COVID-19 pandemic, as well as post-acute COVID-19 syndrome, may have further impacted sickness absenteeism. Conclusion By examining the various risk factors of sickness absenteeism, especially in the post-COVID-19 pandemic era, this research will inform future targeted interventions to reduce sickness absenteeism among Malaysian nurses and its associated consequences.